Controlling aflatoxin contamination - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Contamination of maize grain by the fungus, Aspergillus flavus, is reaching worrying levels in many areas of West Africa. This infection of grain may be responsible for the rising number of nutritional disorders of children as the fungal toxins, or...